Exploring nurses? experiences in community mental health care delivery during the covid-19 pandemic: a qualitative study in the Accra metropolis - Morson, Nana (Department of Psychiatry and Mental Health, 2024)
Mental health care in Ghana recently shifted from a focus on institutional care to the inclusion of community-based care. This shift helped to broaden the scope of mental health care in the country through the establishment of community psychiatric units in most regional and district health facilities across the country. Mental health nurses are posted to these units, and their work includes visiting clients in their homes for reviews (a formal assessment and evaluation of the patient's health, progress, and medication) and follow-ups, health education and case finding. The COVID-19 pandemic however affected the activities of the community mental health nurses due to the implementation of lockdowns and other restrictions. This study explored the experiences of community mental health nurses during the COVID-19 pandemic. The objectives of the study were to investigate nurses' perspectives on how the COVID-19 pandemic has affected community mental health care delivery, to assess the nurses' views on the barriers and facilitators of mental health care delivery during the pandemic and to explore the nurses' recommendations for improving community mental health care (CMHC) in the context of the COVID-19 pandemic and beyond. Fifteen community mental health nurses from five health facilities in the Accra metropolis were interviewed. Thematic analysis of the data was conducted using NVivo software. Findings suggested that the nurses had to suspend most direct-contact community-based activities and instead conducted patient reviews via telephone. They also maintained a limited amount of clinic-based care. COVID-19 had a major impact on CMHC delivery through the suspension of health education and home visits, the move towards clinic-based only reviews, financial constraints, the unavailability of medicines and the reassigning of staff to provide COVID support. The nurses mentioned several barriers to CMHC, both prior to and during the pandemic, including financial and logistical constraints such as lack of transportation, infrastructure and inadequate personal protective equipment (PPE). These challenges were overcome through the nurses' commitment and dedication to their work, as well as the provision of periodic support from the health facilities. The nurses however recommended that there should be sustained logistic and health systems support, an increase in the use of technology, provision of medical aid for mental health, increased mental health education and promotion and incentives for community health workers to help improve CMHC amid any pandemic. In conclusion, the COVID-19 pandemic served to highlight pre-existing issues with CMHC in Ghana. To improve these services, it may be appropriate to take the following steps, among others: increasing funding for mental healthcare in the midst of any pandemic; training more mental health professionals and integrating mental healthcare into primary care. Additionally, it is recommended that further research on community mental healthcare and issues related to it may help to increase access to care and prepare the CMHC system for any potential pandemics.